Reduction in alcohol consumption and health status - Liang, Wenbin; Chikritzhs, Tanya (Wiley-Blackwell Publishing Ltd., 2010)
Aims: This study investigated the association between alcohol consumption and health status using cross-sectional national survey data. Measurements and design: This study relied upon self-report data collected by the 2004 and 2007 Australian National Drug Strategy Household (NDSH) surveys. Households were selected using a multi-stage, stratified-area, random sample design. Both surveys used combinations of the drop-and-collect and computer-assisted telephone interview approaches. Respondents were questioned about their current and past drinking, the presence of formal diagnosis for specific diseases (heart disease, type 2 diabetes, hypertension, cancer, anxiety, depression) and self-perceived general health status. Associations between drinking status, the presence of diagnoses and self-perceptions of general health status among respondents aged 18+ and 45+ were assessed using multivariate logistic regression. Setting and participants: Male and females aged 18 years or older and resident in Australia. The sample sizes for the 2004 and 2007 NDSH surveys were 24 109 and 23 356, respectively. Findings: Respondents with a diagnosis of diabetes, hypertension and anxiety were more likely to have reduced or stopped alcohol consumption in the past 12 months. The likelihood of having reduced or ceased alcohol consumption inthe past 12 months increased as perceived general health status declined from excellent to poor. Conclusions: Experience of ill health is associated with subsequent reduction or cessation of alcohol consumption. This may at least partly underlie the observed 'J-shape' function relating alcohol consumption to premature mortality.